Building Police Mental Resilience in 2025: The Role of Self-Efficacy and Perceived Organizational Support in Strengthening the Resilience of Samapta Directorate Members - Fitri, Aroviani Amsa; Kusmaryani, Rosita Endang; Rosul, Ahmad; Nizam, Zain (World Psychology, 2025)
Working as a police officer requires readiness to face the risk of danger and heavy workload, high pressure when facing threats and uncertain situations. This study was motivated by the phenomenon of the discovery of a low level of resilience of police members. Self-efficacy and perceived organizational support are assumed to be supporting factors in the formation of resilience of police members of the Samapta Directorate. This study aims to examine the role of self-efficacy and perceived organizational support in increasing the resilience of police members of the Samapta Directorate of the DIY Regional Police. This study uses a quantitative method with an explanatory survey research type. The sample of this study used 122 members of the Samapta Directorate of the DIY Regional Police who were selected using the proportionate stratified random sampling technique. Resilience was measured using the CD-RISC 10 scale, self-efficacy is measured by the GSE scale and POS is measured by the SPOS scale. Hypothesis testing using multiple regression analysis with the help of JASP 19.3 program. The results of the study indicate that self-efficacy and perceived organizational support have a significant effect on resilience and are proven to be factors in forming the resilience of members of the Samapta Directorate.